2016
DOI: 10.1007/s10865-016-9762-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of appraisal and coping style in relation with societal participation in fatigued patients with multiple sclerosis: a cross-sectional multiple mediator analysis

Abstract: To determine the relationship between appraisal and societal participation in fatigued patients with Multiple Sclerosis (MS), and whether this relation is mediated by coping styles. 265 severely-fatigued MS patients. Appraisal, a latent construct, was created from the General Self-Efficacy Scale and the helplessness and acceptance subscales of the Illness Cognition Questionnaire. Coping styles were assessed using the Coping Inventory Stressful Situations (CISS21) and societal participation was assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(98 reference statements)
1
5
0
Order By: Relevance
“…The results of our study are consistent with other studies that have shown that people’s evaluation of their situation relates to their autonomy in participation [10, 27]. More specifically, our results indicate that perceptions of one’s health condition matter when it comes to social participation and autonomy in participation.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study are consistent with other studies that have shown that people’s evaluation of their situation relates to their autonomy in participation [10, 27]. More specifically, our results indicate that perceptions of one’s health condition matter when it comes to social participation and autonomy in participation.…”
Section: Discussionsupporting
confidence: 92%
“…Performance expectancy was assessed with 4 items used by Hennemann et al [35], which we adapted to assess expected outcomes in connection to the perceived usefulness or helpfulness of MS apps. Because social participation is essential for successful adjustment to MS [50], a fifth item was added to the survey (“Using MS apps could help me maintain social contacts.”).…”
Section: Methodsmentioning
confidence: 99%
“…The mRS comprises a scale ranging from 0 (no symptoms) -5 (a severe disability) (Yuan et al, 2020). The mRS score has been tested to correlate with the severity of acute brain damage and impairment (Tornbom et al, 2018).…”
Section: Multidimensional Scale Of Perceived Social Support (Mspss)mentioning
confidence: 99%
“…Studies on stroke patients have consistently found that individual participation was a powerful predictor of one's quality of life and life satisfaction (Bergstrom et al, 2015;Chou, 2015). Autonomy has been found to be a fundamental precondition for active participation and was described as 'the ability to make choices, to feel in control of which activities to engage in and in what manner these activities are performed' (Tornbom et al, 2018).…”
Section: Introductionmentioning
confidence: 99%